Clarendon Enterprise - February 20, 2003 - (:unkn) unknown (My University, 2003)
Microfilm provided by the Panhandle-Plains Historical Museum and Clarendon ISD.
The Clarendon News changed names to the Clarendon Enterprise in March of 1996.
Keywords: Clarendon Enterprise.; Clarendon (Tex.)--Newspapers.; Donley County (Tex.)--Newspapers.